The Role of Government in Combating Cyberbullying: Public Policy Challenges in the Digital Age - Arief Rahman Hakim; Aisyah Septianingsih (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
This study examines a phenomenon that has become increasingly common in recent times—digital-based bullying, or cyberbullying, which frequently occurs on social media platforms. The purpose of this study is to identify the various forms of cyberbullying, explore its underlying causes, and evaluate its impacts on victims—particularly children and adolescents. This research employs a descriptive qualitative approach, with data collected through observations of social media activities, as well as reviews of academic journals, media reports, and government policy documents. The findings indicate several prevalent forms of cyberbullying, including insults, hoax dissemination, verbal harassment, physical appearance-related comments (body shaming), and doxing. The main contributing factors to these behaviors include the anonymity provided by the digital world, low understanding of digital ethics and literacy, a lack of empathy, peer group influence, and a history of being victims of bullying. The impacts of cyberbullying are quite serious, manifesting in mental health issues, excessive anxiety, heightened insecurity, decreased motivation for life, and lower academic performance. Therefore, addressing this issue requires collaborative efforts among various parties—families, educational institutions, communities, social media providers, and government agencies. Preventive measures can be implemented through digital ethics education and the enhancement of social literacy to create a healthier and safer digital environment for children and adolescents